Cis requirements for alternative splicing of the cardiac troponin T pre-mRNA. - Cooper, T A (1988)
The cardiac troponin T (cTNT) pre-mRNA splices 17 exons contiguously but alternatively splices (includes or excludes) the fifth exon. Because both alternative splice products are processed from the same pre-mRNA species, the cTNT pre-mRNA must contain cis-acting sequences which specify exon 5 as an alternative exon. A cTNT minigene (SM-1) transfected into cultured cells produces mRNAs both including and excluding exon 5. The junctions of exons 4-5-6 and 4-6 in the cTNT minigene mRNAs are identical to those of endogenous cTNT mRNAs and no other exons are alternatively spliced. Thus, the SM-1 pre-mRNA is correctly alternatively spliced in transfected cells. To circumscribe the pre-mRNA regions which are required for the alternative nature of exon 5, we have constructed a systematic series of deletion mutants of SM-1. Transfection of this series demonstrates that a 1200 nt pre-mRNA region containing exons 4, 5, and 6 is sufficient to direct alternative splicing of exon 5. Within this region are two relatively large inverted repeats which potentially sequester the alternative exon via intramolecular base-pairing. Such sequestration of an alternative exon is consistent with models which propose pre-mRNA conformation as being determinative for alternative splicing of some pre-mRNAs. However, deletion mutants which remove the majority of each of the inverted repeats retain the ability to alternatively splice exon 5 demonstrating that neither is required for cTNT alternative splice site selection. Taken together, deletion analysis has limited cis elements required for alternative splicing to three small regions of the pre-mRNA containing exons 4, 5, and 6. In addition, the cTNT minigene pre-mRNA expresses both alternative splice products in a wide variety of cultured non-muscle cells as well as in cultured striated muscle cells, although expression of the cTNT pre-mRNA is normally restricted to striated muscle. This indicates that cis elements involved in defining the cTNT exon 5 as an alternative exon do not require muscle-specific factors in trans to function.